BEYOND THE ATTRACTIONS: RETHINKING DIGITAL STRATEGIES FOR DELTA LAKKANG - Hardianti Hardianti; Meidy Putri Utami (Politeknik Pariwisata Makassar, 2025)
Delta Lakkang, located in the heart of Makassar City, is an “urban village” surrounded by rivers that offers natural, cultural, and historical tourism potential. Attractions such as delta landscapes, traditional fishing and farming practices, colonial heritage sites, and local culinary experiences highlight its uniqueness. However, tourism development and marketing efforts remain sporadic, relying mostly on local initiatives without an integrated strategy. This study employed a descriptive qualitative approach to analyze tourism marketing in Delta Lakkang. Data were collected through field observations using a tourism attraction checklist, in-depth interviews with stakeholders, and secondary sources from scientific publications and digital media. The qualitative design was chosen to capture the perspectives, experiences, and dynamics among various actors involved in tourism promotion and development. The results indicate major gaps in tourism marketing, including the absence of a master plan, limited use of digital promotion channels, unclear market segmentation, weak branding, and insufficient stakeholder coordination. Key barriers include limited funding, lack of human resource capacity, and minimal institutional support. To overcome these challenges, the study suggests formulating a comprehensive marketing strategy, strengthening destination branding, providing digital marketing training for local tourism groups (Pokdarwis), and enhancing collaboration among government, community, and private stakeholders. Positioned within the framework of urban maritime tourism, Delta Lakkang has strong potential to serve as an alternative destination in Makassar, enriching maritime tourism experiences beyond beaches and islands. Strengthening digital promotion and empowering local communities are considered crucial strategies for developing Delta Lakkang into a sustainable urban maritime tourism destination.